THE FACTORS THAT INFLUENCE MUSLIM TOURISTS' DECISIONS IN CHOOSING HALAL TOURISM DESTINATIONS (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
The halal tourism industry has grown rapidly as a strategic segment of the global economy. This study identifies and synthesizes the factors that influence Muslim tourists' decisions in choosing halal tourism destinations. A systematic literature review (SLR) approach will be employed. A comprehensive review of 16 articles indexed in Garuda, Scopus, ScienceDirect, and SINTA was conducted between 2016 and 2025 to analyze the relevance of topics, methods, and variables related to Muslim tourist behavior. The study found seven primary categories of factors that influence travel decisions: religious, social and cultural, psychological and perceptual, and economic and accessibility factors. Religious factors predominantly influence tourist preferences, while social, psychological, and economic factors reinforce travel decisions. The study proposes a conceptual model in which religiosity is the central variable, with the other three factors functioning as complementary moderators. These findings contribute to the development of halal tourism theory and practice by emphasizing the importance of a holistic approach that integrates spiritual, social, and economic values to enhance the competitiveness and sustainability of halal destinations at the global level.